The Impact of Negotiation Skills in Meeting Management Among Heads of Departments in Pure Education College - Wiam Wahab Abdul-Hussain (University of Thi-Qar Journal, 2021)
The current study aimed at identifying the effect of negotiation skills in meeting management among department heads and the teaching staff at the College of Pure Education / Dhi-Qar University, in order to achieve the goals pursued where the researcher used the descriptive approach that is characterized by field study and through which she distributed a questionnaire to find the relationship and influence of research variables Included in the first variable, negotiation skills from which two skills were chosen, namely the skill of influence and persuasion and the communication skill corresponded to the management of meetings after verifying the validity of the questionnaire used and the validity of stability, as this questionnaire was applied and distributed to A sample consisted of (82) academic persons distributed between heads of departments and teaching staff at the College of Pure Education / Dhi-Qar University. Significant significance between the search variables.